INFLUENCE OF THERAPEUTIC EXERCISES ON THE BODY COMPOSITIONE OF PATIENTS WITH HIV-POSITIVE STATUS (LITERATURE REVIEW) - Orfin, A. Ya.; Mazepa, M. A. (Rehabilitation and Recreation, 2022)
Several studies have reported the benefits of exercise for adults with HIV, although there is no consensus on the most effective methods. The aim was to determine the impact of different types of therapeutic exercises on body structure in HIV patients through a systematic strategy for finding randomized controlled trials. Material and methods. Literature sources were searched in the databases PubMed, Cochrane Library, and PEDro for 2000–2020. We selected randomized controlled trials that examined the effects of exercise on body structure, and muscle strength in adult patients with HIV-positive status. The PEdro scale was used to assess methodological quality. 15 randomized controlled trials (RCTs) were selected for analysis in this review. Results. Studies have shown the effect of therapeutic exercises on the body structure of people living with HIV (PLHIV). Thus, a positive effect on the functional parameters of muscle tissue was found, but the achievements were specific to different types of therapeutic exercises and their combinations. Resistance training has greatly improved your body structure and muscle strength. Aerobic exercise has shown a greater effect on the reduction of adipose tissue. The use of a combination of strength and aerobic therapeutic exercises in the training program had a positive effect on all indicators studied. Although there is an ongoing debate about the intensity and duration of combined therapeutic exercises to achieve such results.